Role of integrins in the development of fibrosis in the trabecular meshwork - Faralli, Jennifer A.; Filla, Mark S.; Peters, Donna M. (Frontiers in Ophthalmology, 2023)
Primary open angle glaucoma (POAG) is a progressive and chronic disease exhibiting many of the features of fibrosis. The extracellular matrix (ECM) in the trabecular meshwork (TM) undergoes extensive remodeling and enhanced rigidity, resembling fibrotic changes. In addition, there are changes associated with myofibroblast activation and cell contractility that further drives tissue fibrosis and stiffening. This review discusses what is known about the integrins in the TM and their involvement in fibrotic processes.